1996
DOI: 10.1183/09031936.96.09050952
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of nasal continuous positive airway pressure on reversible or fixed upper and lower airway obstruction

Abstract: Our study was to assess whether there were differential effects of nasal continuous positive airway pressure (nCPAP) on different kinds of obstruction in either upper or lower airways in patients with chronic obstructive pulmonary disease (COPD). nCPAP (6 cmH 2 O for ten minutes) was applied to 7 patients with reversible extrathoracic upper airway obstruction (RUAO) and 3 patients with fixed extrathoracic upper airway obstruction (FUAO). Eighteen stable asthmatics, receiving methacholine challenge to induce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…There was a report that symptoms of extrathoracic airway obstruction such as stridor and dyspnea were significantly improved according to 20-30% increase of PIF in patients with reversible extrathoracic airway obstruction (22). Also, PIF is a very simple method to detect inspiratory flow limitation when a pattern of variable extrathoracic airway obstruction is observed in the flow-volume curve.…”
Section: Discussionmentioning
confidence: 99%
“…There was a report that symptoms of extrathoracic airway obstruction such as stridor and dyspnea were significantly improved according to 20-30% increase of PIF in patients with reversible extrathoracic airway obstruction (22). Also, PIF is a very simple method to detect inspiratory flow limitation when a pattern of variable extrathoracic airway obstruction is observed in the flow-volume curve.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown that nCPAP induces a decrease in the MEF 50 /MIF 50 ratio and an increase in PIF and forced inspiratory vital capacity, as well as a dramatic improvement of symptoms in patients with reversible upper airway obstruction due to vocal cord paralysis or edema [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Positive pressure application may also prevent bronchospasm induced by various stimuli. Prior reports showed that methacholine and histamine induced bronchospasm could be averted by application of CPAP [41,42]. WILSON et al [43] have demonstrated that externally applied PEEP prevents exercise induced asthma.…”
Section: Effects Of and Rationale For Application Of Positive Pressurmentioning
confidence: 99%